2021
DOI: 10.3390/molecules26154474
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Components, Volatile Profile and In Vitro Antioxidative Properties of Taxus baccata L. Red Arils

Abstract: This study aimed at assessing the composition of bioactive compounds, including ascorbic acid, carotenoids and polyphenols, the volatile compound profile and the antioxidant activity of red arils (RAs) of Taxus baccata L. grown in diverse locations in Poland. Among the carotenoids assayed in high quantities (3.3–5.42 μg/g), the lycopene content (2.55–4.1 μg/g) was remarkably higher than that in many cultivated fruits. Samples collected from three sites were distinguished by higher amounts of ascorbic acid (125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Depending upon the experimental condition and essential oil composition, synergistic or antagonistic behavior is expected and exceptions may be obtained [31] and this could be an area of further exploration in CEO. Moreover, phenolic compounds such as polyphenols and phenylpropanoids, which are sometimes among the main components of essential oil, have been found to have higher antioxidant values [31,32]. Additionally, the major constituents of CEO, limonene, and β-pinene, have a grounded defensive activity against many kinds of malignant growth as reported in the literature [33].…”
Section: Antioxidant Activity Of Ceosmentioning
confidence: 93%
“…Depending upon the experimental condition and essential oil composition, synergistic or antagonistic behavior is expected and exceptions may be obtained [31] and this could be an area of further exploration in CEO. Moreover, phenolic compounds such as polyphenols and phenylpropanoids, which are sometimes among the main components of essential oil, have been found to have higher antioxidant values [31,32]. Additionally, the major constituents of CEO, limonene, and β-pinene, have a grounded defensive activity against many kinds of malignant growth as reported in the literature [33].…”
Section: Antioxidant Activity Of Ceosmentioning
confidence: 93%
“…Fruit volatiles consist of compounds from various chemical groups (alcohols, aldehydes, esters, ketones, furanones, and terpenes), which are formed from precursors as the fruit ripens and changes postharvest [ 24 ]. For example, sucrose content is associated with the production of furans, whereas fatty acids content is related to the synthesis of esters and alcohols through lipid degradation [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flavor volatiles of New Zealand tamarillo were dominated by eight different types of alcohols with 2,3-butanediol as the most abundant ( Table 2 ). This volatile was also present in Colombian tamarillo with relative amount of <100 μg/kg FW [ 7 , 18 ] and was also found as one of dominating alcohol in other fruit, such as Taxus baccata L. Red Arils [ 24 ]. Eugenol and α-terpineol, the major volatiles in tamarillo from Colombia [ 7 , 18 ], Malaysia [ 8 ], and Panama [ 6 ], were identified in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The populations of Serbia studied by Stefanović et al (2016) and those from Turkey studied by Yasar (2013) are dominated by alcohol; while the population of Serbia studied by Radulovic et al (2011) was found, dominated by monoterpenoids. A recent study on T. baccata red arils in Poland showed that alcohols, ketones, esters and aldehydes are dominated in their volatile profile (Tabaszewska et al 2021). The intra-specific difference of the chemical composition can be justified by the diversity of environmental and geographic parameters as well by the harvest period (Aboukhalid et al 2017;Yeddes et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant test of methanolic extracts obtained from T. baccata in Serbia shows that the plant has significant DPPH scavenging activity (Milutinović et al 2015). A study on the bioactive compounds found in red arils of T. baccata, shows that they have an important antioxidant capacity to scavenge DPPH (Tabaszewska et al 2021). Taxus baccata can be considered as a source of natural antioxidants due to its strong antioxidant capacity (Guleria et al 2013).…”
Section: Discussionmentioning
confidence: 99%